PERAMALAN HASIL PANEN JAGUNG DI KECAMATAN SOLOKURO DENGAN MENGGUNAKAN METODE TREND MOMENT - Rihatul Janah; Ahmad Isroil; Aris Alfan; Mohammad Nurul Alamin; Shyndy Sarwinda Mas Ayu (Jurnal Matematika dan Sains (JMS), 2021)
As an agricultural country, Indonesia relies on the agricultural sector in almost all of its territory, including in Solokuro District, Lamongan Regency, East Java. The agricultural sector is the mainstay sector because this sector plays a role in providing food for the community. The plant that is widely cultivated as well as a staple food in Indonesia is corn. Corn is the second food crop after rice, even in some areas growing corn is more profitable than growing rice. In Solokuro Subdistrict itself corn is a superior crop, to find out the amount of harvest in the future, you can use the trend moment method. The trend moment method is a method used for forecasting or prediction. The data used in this study is corn harvest data in Solokuro District in 2017-2019 to predict maize yields in Solokuro District in 2022.